Jnfluence of ecdysteroid muristerone A on the development of Ephestia kuehniella Zeller (Lepidoptera Phycitidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
The contamination of the rearing medium of Ephestia kuehniella Zeller (Lepidoptera Phycitidae) with ecdysteroid muristerone A influences whole development of insect producing a high mortality rate in the first larval instar, irregular duration of the other instars, morphological changes (malformations) in adults, lowering of egg-hatching.Moreover, as a proof of influence of moulting hormones on gametogenesis and on fertility, we saw these effects also in offspring of treated pairs, but reared on untreated substrate.This far-reaching effect lowers or disappears in the next generation, which tends to normality.